«Ripartire da Cristo» - Xerri, Daniel (Alpha Omega, 2018)
Summary: Theology has often spoken of the «living actuality» of Christ and of the «eternal challenge of the Gospel». The figure of Jesus Christ is always new, always actual and has not ever lost its originality and its uniqueness. This truth has more value in our day, characterized by progress, because contemporary man despite his technical progress does not evidence more humaneness. The problem of Jesus is not, however; a «neutral» problem: whoever confronts it, takes into consideration feels that in some way his own person and his own destiny are involved. Therefore, dealing with the problem of Jesus, everyone even without fully realising it inserts his whole self.